2016
DOI: 10.1037/ort0000172
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic socialization, perceived discrimination, and psychological adjustment among transracially adopted and nonadopted ethnic minority adults.

Abstract: Little is known on how transracial adoptees (TRA) navigate issues of race and ethnicity. Using Shared Fate Theory as a framework, this study was interested in the moderating role of adoption status among a group of ethnic minority adults in explaining the relationship between ethnic socialization, perceived discrimination, and mental health outcomes. Nonadopted (NA; n = 83) and TRA (n = 87) ethnic minorities responded to measures on ethnic socialization, perceived discrimination, and psychological outcomes adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 59 publications
1
25
0
Order By: Relevance
“…Ethnic socialization has also been found to have a protective role against the adverse effects of discrimination on mental health status through pathways, such as increasing self-esteem, ethnic identity, or bicultural self-efficacy [25,64,67]. Such ethnic socialization and social networks may provide the necessary social and emotional support needed to combat negative internalization of discrimination and poor mental health outcomes [68].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethnic socialization has also been found to have a protective role against the adverse effects of discrimination on mental health status through pathways, such as increasing self-esteem, ethnic identity, or bicultural self-efficacy [25,64,67]. Such ethnic socialization and social networks may provide the necessary social and emotional support needed to combat negative internalization of discrimination and poor mental health outcomes [68].…”
Section: Resultsmentioning
confidence: 99%
“…While much work remains to be done in this arena, studies among youth and young adults may shed light on the importance of discrimination at critical developmental points along the life course. Several studies have shown that adolescents and young adults experiencing racial or ethnic discrimination were at greater risk of depression, anxiety, alcohol and cigarette use, victimization, aggression, violent behaviors, and suicidal ideation [30,36,43,47,52,67,7683]. Certain groups of adolescents, such as African American boys, appeared to be more frequent targets for racial discrimination as they aged [81].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a subset of studies found that the associations between preparation for bias and indicators of adjustment were dependent on context, including indicators of parenting relationships, family context, and neighborhood characteristics (e.g., Arnold, Braje, Kawahara, & Shuman, ; Burt, Simons, & Gibbons, ; Dunbar et al, ; Grindal, ; Kiang et al, ; Lambert, Roche, Saleem, & Henry, ; Tang, McLoyd, & Hallman, ; Tran, Mintert, & Jew, ; Wang & Huguley, ). For instance, higher preparation for bias was associated with higher depressive symptoms among African American adolescents but only in families in which the quality of the mother–adolescent relationship was poor; in families with high trust and communication in the mother–adolescent relationship, preparation for bias was not associated with depressive symptoms (Lambert et al, ).…”
Section: Associations Between Family Ethnic–racial Socialization and mentioning
confidence: 99%
“…In recent years, the adoption literature has evidenced that, like immigrants, international transracial adoptees are likely to experience discrimination in their everyday life, as they often look different from the nonadoptive population (Lee & the Minnesota International Adoption Project Team, ; Riley‐Behringer, Groza, Tieman, & Juffer, ; Rosnati & Ferrari, ). Some studies have demonstrated that perceived discrimination affects adoptees on a number of different psychosocial dimensions, increasing the levels of both internalizing and externalizing problems, drug and alcohol abuse (Lee, Lee, Hu, & Kim, ), depression (Arnold, Braje, Kawahara, & Shuman, ), psychological distress, and sleep issues (Koskinen et al, ).…”
Section: Perceived Discrimination and Well‐beingmentioning
confidence: 99%
“…To date, studies comparing the experiences of immigrants and international transracial adoptees have been limited in number, have been carried out only in the United States, and have shown inconsistent results. For instance, whereas Seol et al () indicated that adopted Korean American adolescents reported lower levels of perceived racial discrimination than nonadopted Korean American adolescents, Arnold et al () reported similar levels of perceived discrimination among emerging adult and adult adoptees, compared to nonadopted ethnic minority individuals. Moreover, there is no empirical evidence that the impact of perceived ethnic discrimination on well‐being is similar for both groups.…”
Section: Perceived Discrimination and Well‐beingmentioning
confidence: 99%